Tiruttoṇṭar Periyapurāṇam : itu kaṟṟōrum maṟṟōrumākiya yāvarukkum eḻitilēpayaṉpaṭumporuṭṭu Ārumukanāvalaravarkaḷāl kattiya rūpamākac ceyyappaṭṭatu - Āṟumuka Nāvalar, 1822-1879 (SAMP early 20th-century Indian books project, 1928)
Prose rendering of Periyapurāṇam, by Cēkkiḻār, 12th century Śaivite leader, verse hagiography of Tamil Śaivite leaders from South India.